Strategies for Empowering Local Product Msmes In Facing Competition With Imported Foreign Products - Guntur Wahyudi; Rosyidin Kurniawan; Moh Andrean Umami; Mashudi (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) serve as the backbone of Indonesia’s economy, contributing significantly to employment creation, income distribution, and national economic growth. However, in the face of globalization and free trade, MSMEs struggle with intense competition from low-cost and high-quality imported products. This study aims to explore strategies for empowering local MSMEs to effectively compete against foreign goods in both domestic and international markets. Utilizing a qualitative descriptive method supported by literature review and policy evaluation, the research adopts a systematic approach involving multi-stakeholder synergy. Findings reveal that MSME empowerment must focus on enhancing access to finance, improving human capital, embracing digital technology, and optimizing marketing strategies. Government support in the form of adaptive regulations, robust infrastructure, and fiscal incentives is crucial to strengthening MSME competitiveness. Furthermore, the integration of information technology reduces transaction costs and significantly boosts market reach. The article proposes a collaborative empowerment model involving government, financial institutions, industry players, and civil society to foster a resilient, export-oriented MSME ecosystem.